Study On Waste Management In Makale Market And Its Impact On The Community In Tana Toraja Regency - -, Roland Tandiongan; Abdul Manan; La Ode Siwi; Muhammad Saleh Qadri (International journal of technology and education research, 2025)
Waste management is a very serious environmental problem faced by Indonesian society due to the increasing amount of waste generated in Indonesia. The purpose of this study was to determine or evaluate waste management at Makale Market and its impact on the community in Tana Toraja Regency. This study used several methods: cluster technique was used to group traders who would become samples, the Slovin formula was used to determine the number of samples to be studied, and descriptive analysis was used to analyse waste management at the market by market managers, trader behaviour, and the impact on the surrounding community by collecting data through observation, interviews, documentation, and literature study. The results of the study show that waste management at Makale Market does not yet meet the criteria (SNI 19-2454-2002) in terms of containment (organic and inorganic waste is still mixed), collection (there is a collection schedule), transfer (transfer is carried out every day), management (no recycling is carried out), and final disposal (the equipment used is adequate). The impact on the community (discomfort) requires the Tana Toraja Regency Environmental Agency to provide more full support for waste management, especially at Makale Market in Tana Toraja Regency, South Sulawesi.